Hubungan Antara Dukungan Sosial Keluarga Dan Pola Asuh Demokratis Orang Tua Dengan Kematangan Emosi Pada Siswa Kelas XI SMA Negeri 12 Tangerang Selatan - Saragih, Chantika Putri Ramadhani; Herdajani, Febi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study is a quantitative study that aims to determine the relationship between family social support and parents’ democratic parenting with the emotional maturity of SMA Negeri 12 South Tangerang. The sampling technique in this study is probability sampling with research subjects as many as 160 respondents. The data collection method uses scales, namely emotional maturity scales, family social support, and democratic parenting using Bivariate Correlation analysis techniques with the SPSS 27.0 for windows program. Analysis of family social support with emotional maturity had results with a value of R = 415 p = 0.000 and a relationship between democratic parenting of R = 0.311 p = 0.000. This means that there is a significant positive relationship between family social support and emotional maturity and there is also a significant positive relationship between democratic parenting and emotional maturity . Furthermore, the results of data analysis tests with Multivariate Correlation to measure the relationship between family social support and democratic parenting obtained values R = 0.423, R square 0.179 and p = 0.000 (p < 0.05). This shows that there is a relationship between family social support and democratic parenting with emotional maturity in Class XI students of SMA Negeri 12 South Tangerang.